Spindle cell epithelioma of the vagina with rare morphology: a case report and literature review - Tang, Xian-bin; Xu, Yuan-gui; Yao, Li; Yuan, Ling-ling; Huang, Yu-gang (Frontiers in Oncology, 2025)
Spindle cell epithelioma of the vagina (SCEV) is a rare female genital tract neoplasm with a complex morphology and immunophenotype easily resulting in misdiagnosis. The tumor was primarily composed of spindle and epithelioid cells. In this case, there was no obvious epithelial component in the tumor parenchyma, and only epithelioid cells with rounded nuclei were observed, which were tightly mixed with the spindle cells. Here, we describe a unique case of vaginal spindle cell epithelioma in a 51-year-old woman. In this tumor, mucoid degeneration and the formation of vacuoles or microcysts with varying sizes without epithelial lining were observed, and only a few glandular structures were observed in the periphery of the tumor. Immunohistochemical staining showed diffuse positivity for AE1/AE3, CK7, and CD10 in both spindle and epithelioid cells, and ER, PR, P63, and P40 were diffusely expressed in the spindle cells, while expressed to varying extents in epithelioidal cells. CD34 was expressed focally in spindle cells. No expression of Desmin, SMA, CD31, Caldesmon, TLE-1, WT-1, and SS18 was in the tumor, which could be differentiated from synovial sarcoma. Tumor cells were negative for S100 and positive for CD10 and BCL2 in their mesenchyme. There are conflicting reports on the tissue origin of SCEV, and the immunohistochemical staining of this case supports the hypothesis that SCEV originates from multipotent stem cells.